Related variety, unrelated variety, and regional growth: The role of absorptive capacity and entrepreneurship - Michael Fritsch; Sandra Kublina (Friedrich Schiller University Jena, 2016)
This paper investigates the effect of related and unrelated variety on regional growth in West Germany. In particular, we analyze the role of regional absorptive capacity and new business formation for these effects. We find that West German regions benefit from both types of varieties. The positive effect of unrelated variety on growth is more pronounced in regions with higher levels of absorptive capacity in terms of R&D activities and with higher levels of new business formation. Such moderating effects cannot be found for related variety.
Keywords: R11; R12; D62; 330; related variety; unrelated variety; knowledge spillovers; regional absorptive capacity; entrepreneurship; regional growth